Comparative study between probiotics isolated from giant freshwater prawns and giant tiger prawns in improving the health of nile tilapia (Oreochromis nilotius). (December 2018) - Feliatra, F; Lukistyowati, I; Nursyirwani, N; Melina, D; Ramadhani, M
Abstract: One of bacterial diseases frequently attacking Nile tilapia ( Oreochromis niloticus ) is caused by Streptococcus iniae . This research aims to analyse the impact of immersion of probiotic bacteria isolated from giant freshwater and giant tiger prawns, towards the health of Nile tilapia. The research was conducted from February to June, 2017. The completely randomized design was employed method, with 5 treatment phases and 3 repetition. The probiotic provision treatment to Nile tilapia was executed by immersing it for 5 minutes in every 10 days for 30 days of culture. The probiotic density used was 10 5 CFU/ml. Subsequent to the 30 days of culture, an infection with Streptococcus iniae bacteria was carried outin an intramuscular technique with 0.1 ml/fish and 10 5 CFU/ml density. The research result reveals that the probiotic provision, either from giant freshwater or giant tiger prawn shows a positive indication towards the health of Nile tilapia, observed from parameters like the number of red blood cells, hemoglobin level, hematocrit level, total leucocytes and survival rate. The P3 treatment is the best treatment with total erythrocytes as 174.67x10 4 sel/mm 3, 7.47 g/dL hemoglobin, 33.67%, hematocrit, 80.00x10 3 sel/mm leucocytes. The immersion with probiotic bacteria could enhance the health quality of Nile tilapia.